The HIV pandemic local and global implications - Beck, Eduard J., 1955- (Oxford : Oxford University Press, 2008)
A quarter of a century into the HIV pandemic, this multi-country comparative book demonstrates how the response to a common, global threat is shaped by the history, culture, institutions and health systems of individual nations.
Originally published: 2006.
Description based on print version record.
Includes bibliographical references and index.
Keywords: AIDS (Disease) -- International cooperation; HIV infections -- International cooperation